Improving Student Physical Fitness Through the Indonesian Student Fitness Test (TKPN) as a Basis for Sports Development in Indramayu Regency - Fitranto, Nur; Irawan, Andri; Hasibuan, Muchtar Hendra; Prabowo, Eko; Paranoan, Andri; Fadillah Amin, Bazuri; Andri, Gusti (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Abstract: The aim of this activity is to provide practical field experience in measuring physical fitness for students. The PKM method used is a direct demonstration by collecting student fitness data by PJOK Indramayu teachers. The results of community service using the direct measurement method for a sample of junior high school students showed that the fitness level for the male category was in the Fair category with a scale value of 2.13 and the fitness level for the female category was in the Adequate category with a scale value of 2.65. It is hoped that with this measurement, physical education and health sports teachers in Indramayu district will become more enthusiastic in developing fitness and improving the quality of children's movements so that the quality of children's thinking and creativity in learning and socializing will increase.